Largely invariant communities of bacterial endophytes in the nonphotosynthetic mycoheterotrophic plant Pterospora andromedea. Issue 11 (24th November 2021) - Miller, Steven L.; Gans, Maya R.
Abstract: Premise: Mycoheterotrophic plants rely on fungi to obtain their carbon requirements. Recent experiments demonstrated the presence of endophytic bacteria associated with mycoheterotrophs. Although mycoheterotrophs show high specificity for their fungal partners, it is not known whether they also show high specificity for associated bacteria or whether the bacteria have a definite function in the symbiosis. Methods: Two 16S rRNA sequencing experiments were designed to explore endophytic microbial community composition and function in root ball fractions of the mycoheterotroph Pterospora andromedea (Ericaceae), and rhizosphere soil and control soil 5 m away from each plant. One experiment compared microbial assemblages in fractions of six plants to those in rhizosphere and control soil samples. Another experiment documented bacterial endophyte diversity in root balls of 97 plants from across North America. Results: Soil samples were similar in bacterial community structure but were significantly more diverse and less consistently structured than were bacterial communities within root balls. The proportion of endophytic bacterial species varied slightly but not their community composition despite differences in P. andromedea lineage, geography, conifer species, and fungi. Predictive metagenomic profiling of the endophytes in P. andromedea ‐only root ball fractions showed many of the bacterial endophytes likely function in N‐metabolism and N‐fixation. Conclusions: Our results document a consistent and largely invariant community of endophytic bacteria in P. andromedea across biotic and abiotic environmental conditions at a continental scale. It is unknown what role these bacteria may play in the quad‐partite symbiotic network centered on P. andromedea ; however, the predictive metagenomic profiling suggests a possible function in N‐metabolism or N‐fixation. Discovery of a ubiquitous community of endophytic bacteria with a putative function centered on N‐metabolism or N‐fixation could have a previously unrecognized impact on understanding of mycoheterotroph ecophysiology.